2022
DOI: 10.1111/efp.12762
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of Chrysoporthe deuterocubensis isolates from Melastoma and Eucalyptus in Malaysia and Indonesia

Abstract: Chrysoporthe deuterocubensis is the causal agent of a serious canker disease of Eucalyptus spp. in tropical and sub‐tropical areas of Asia. Where the disease occurs, Eucalyptus spp. are non‐native and the native hosts of the pathogen have not been conclusively determined. The chance discovery of C. deuterocubensis on native Melastoma malabathricum growing in the understory of Eucalyptus trees in Indonesia raised the possibility that this woody shrub could be a native host of C. deuterocubensis, which would the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…myrticola would likewise be new to these trees. A host shift (Slippers et al., 2005) from a native species in the Myrtales to infect the trees reported in this study is a distinct possibility, given the fact that this has occurred for other species in the Cryphonectriaceae (Nakabonge, Roux, et al., 2006; Oliveira et al., 2022; Suzuki et al., 2022).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…myrticola would likewise be new to these trees. A host shift (Slippers et al., 2005) from a native species in the Myrtales to infect the trees reported in this study is a distinct possibility, given the fact that this has occurred for other species in the Cryphonectriaceae (Nakabonge, Roux, et al., 2006; Oliveira et al., 2022; Suzuki et al., 2022).…”
Section: Discussionmentioning
confidence: 70%
“…In the case of Corymbia, species in this genus are relatively new to the South African plantation environment, and the disease caused by X. myrticola would likewise be new to these trees. A host shift (Slippers et al, 2005) from a native species in the Myrtales to infect the trees reported in this study is a distinct possibility, given the fact that this has occurred for other species in the Cryphonectriaceae Oliveira et al, 2022;Suzuki et al, 2022).…”
Section: Discussionmentioning
confidence: 84%